Impact of early mobilization on discharge disposition and functional status in patients with subarachnoid hemorrhage: A retrospective cohort study. Issue 51 (23rd December 2021) - Okamura, Masatsugu; Konishi, Masaaki; Sagara, Akiko; Shimizu, Yasuo; Nakamura, Takeshi
Abstract : Abstract: Whereas early rehabilitation improves the patients' physical function in patients with cerebral infarction and hemorrhage, complications in the early stage are the main barriers in patients with subarachnoid hemorrhage (SAH). Therefore, the clinical impact of early rehabilitation in patients with SAH is not well documented. We sought to investigate whether early mobilization is associated with favorable discharge disposition and functional status in patients with SAH. Hospitalization data of 35 patients (65.7 ± 13.7 years, 37.1% men) were retrospectively reviewed. The early and delayed mobilization groups were defined as those who had and had not participated in walking rehabilitation on day 14, respectively. We investigated whether patients were discharged or transferred to another hospital and assessed their functional status using the Functional Ambulation Categories, Ambulation Index, Glasgow Outcome Scale, and modified Rankin Scale scores. Nine patients (69.2%) in the early mobilization group and one patient (4.5%) in the delayed mobilization group were discharged home directly ( P < .001). In multivariate logistic regression analysis, early mobilization was independently associated with home discharge after adjustment using the World Federation of Neurosurgical Societies grade (adjusted odds ratio = 30.20, 95% CI = 2.77–329.00, P < .01). Early mobilization was associated with favorable functional status at discharge through multivariate linear regression analysis (standardized beta = 0.64 with P < .001 for the Functional Ambulation Category and beta = -0.62 with P < .001 for the modified Rankin Scale, respectively). Early mobilization was associated with home discharge and favorable functional status at discharge. Larger prospective studies are warranted. Abstract : Supplemental Digital Content is available in the text